LA GUÍA DE EXPERTOS COMO HERRAMIENTA DE COMUNICACIÓN Y DIVULGACIÓN CIENTÍFICA: GESTIÓN Y DISEÑO EN LA UNIVERSIDAD DE NAVARRA - Dra. Aida María DE VICENTE DOMÍNGUEZ ,Dr. Javier SIERRA SÁNCHEZ (Fonseca, Journal of Communication, 2023)
This study centers on an organizational strategy in relation to media in order to manage tacit knowledge because it is becoming one of the main tasks of every competitive organization in our current era. It focuses on the Expert Guide, a service that allows journalists to localize and establish direct contact with the researchers of an organization in an autonomous manner, which promotes the visibility and image of brands.